Influence of ultrasonic activation in association with different final irrigants on intracanal smear layer removal - Matheus Albino Souza; Felipe Trentin Motter; Tobias Piton Fontana; Marlos Barbosa Ribeiro; Daniela Cristina Miyagaki; Doglas Cecchin (Universidade Estadual de Campinas, 2016)
Aim: To evaluate the influence of ultrasonic activation (US) with different irrigant regimens in smear layer removal. Methods: One hundred bovine incisors were instrumented and divided into ten groups (n=10) according to final irrigation protocols: distilled water (DW); DW+US; 17% EDTA; QMix; 10% citric acid; 37% phosphoric acid; 17% EDTA+US; QMix+US; 10% citric acid+US; 37% phosphoric acid+US. The samples were then submitted to scanning electron microscopy where a score system was used to evaluate the images and effectiveness of proposed treatments. The data were statistically analyzed by Kruskal-Wallis and Mann-Whitney U tests for intergroup comparisons as well as the Wilcoxon and Friedman tests for intragroup comparisons at 5% significance level. Results: In the cervical third, groups 17% EDTA, QMix, 10% citric acid, 17% EDTA+US, QMix+US and 10% citric acid+US were more effective in smear layer removal (p<0.05); in the middle third, groups 17% EDTA+US and QMix+US were more effective in smear layer removal (p<0.05); in the apical third, groups 17% EDTA,17% EDTA+US and QMix+US were more effective in smear layer removal (p<0.05). Conclusions: US can aid 17% EDTA and QMix in smear layer removal at the middle third and QMix at the apical third, contributing to the cleaning of root canal system.